Tinjauan Pemanfaatan Rekam Medis Elektronik Dalam Manajemen Penyakit Ginjal Kronis - Naryanti, Indah; Wijayanta, Setya; Fahyudi, Asharul (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The utilization of Electronic Medical Records (RME) in the management of Chronic Kidney Disease (CKD) offers a range of significant benefits, including improved patient monitoring, reduced medical errors, and improved patient safety. This study aims to review the effectiveness of RME in the management of CKD, identify obstacles in its implementation, and offer recommendations for increasing the use of RME. A qualitative approach was used in this study, with data obtained through in-depth interviews and document analysis. The results of the study show that RME makes it easier for medical personnel to access patient data quickly and accurately, which is very important in the management of CKD. Additionally, RME helps to reduce errors in drug prescription writing and ensure that the patient's medical history is well documented, improving the safety and quality of care received by patients. However, the implementation of RME still faces various obstacles such as high initial costs, resistance to changes from medical staff, and technical issues and interoperability. To address these challenges, it is recommended to provide ongoing training for medical staff, improve technological infrastructure, and support from hospital management